John Robinson and the Beginnings of the Pilgrim Movement - Powicke, Frederick James (Harvard theological review, 1920)
The scope of this article is strictly limited. It takes no account of the great issues, social, national, and international, which, in the course of time, flowed from the few simple folk “in the north parts” of England about Scrooby and Gainsborough who obeyed what they believed to be a divine impulse.Others far more competent for the purpose have already dealt with, or will deal with, these. Nor does it do more than touch the details of the life into which the exiles passed at Amsterdam and Leyden. For on these, Dr. Dexter and his son — to mention but two of the workers in this fieldx — may almost be said to have spoken the last word. Nor does it follow the Pilgrims into the new world where they struck root with such heroic fortitude, except so far as is required to correct one or two somewhat inveterate mistakes. It is, in fact, limited to the man who, beyond any one else, was the chief spiritual influence in those earliest pioneers whose character and ideals imparted a permanent direction to the development of New England. At the same time, while relating the substance of what is known of Robinson, I have tried to state the truth with regard to the circumstances in which the Pilgrim movement took its start; and if, in so doing, it has seemed necessary to criticize adversely the conclusions of one writer in particular, my excuse must be that his narrative has been accepted, in some high quarters, as that of an authority on the subject whose word is final. It is not by any means final, as the sequel, I think, will show.